Padrão de salivação de Cimex lectularius (Hemiptera:Cimicidae) durante as fases da hematofagia na pele do hospedeiro vertebrado - Luiza Rodrigues Moreira Guerra (2020)
Infestations by Cimex lectularius (Hemiptera:Cimicidae), although underreported, have been increasing in recent years in much of the world, becoming an important urban plague without signs of reversion. The health problems caused by these insects, popularly known as bed bugs, are directly associated with the mandatory hematophagous habit and anthropophilia. In addition to the intense itching, the bites can trigger allergic reactions in response to the salivary components deposited on the host's skin during the blood meal. Although cimicid saliva is indispensable in hematophagy, there are no studies on the salivation process of these insects, which is the object of study in the present work. For this, females of C. lectularius (7 days fasting) were fed on hairless mice, and the salivation profile was investigated through intravital microscopy and electromyogram of the cibarial pump. Referring to the characterization of the feeding process, it was observed that the cimicids cannulated both arterioles (59.7%) and venules (43.2%). The initial moment of cannulation of the blood vessel causes a transient vessel contraction, followed by vibration of their wall and a progressive increase of vessel diameter, presented a crisp vasodilation at the end of the blood meal. Hemorrhages were observed in both arterioles and venules, occurring shortly after the removal of the mouthparts of the cannulated blood vessel. The use of intravital microscopy simultaneously with the electromyogram of the cibarial pump, confirmed that the electrical signals identified during engorgement phase are related to the contraction of the muscles associated with the wall of the cibarial pump. From the marking of the content of the main salivary glands of C. lectularius with 0.05% Acridine Orange, it was observed that the cimicids salivate throughout the blood feeding, however, with distinct profile in the probing and engorgement phases. In the probing phase, saliva is released continuously and in greater quantity. In contrast, in the engorgement phase, saliva is released in small quantities at irregular intervals, mostly just near the cannuled vessel wall. In addition, during the engorgement phase, blood intake by the insects can occur independently of the release of saliva.